A method for image recognition of intersectant dual-pointer instrument. (December 2021) - Sun, Yong; Li, Wansheng; Zhao, Yucheng; Ren, Liying; Jiang, Wei
Abstract: Image recognition of pointer instrument based on machine vision has been widely used. However, traditional algorithms are inadequate in the case of intersectant dual-pointer instrument. This paper provides a complete solution, including image pretreatment, extraction of the position of pointer and reading identification. In particular, the target line segment filter method is invented.